Manusia Membutuhkan Agama di Masyarakat - Sunardin Sunardin (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2021)
Religion is one of the most sacred aspects in meeting the standard needs of human life. Humans are the most perfect creatures created by Allah SWT, therefore, humans always need role models to carry out their respective lives. Humans will never feel satisfied with what they already have, therefore humans must meet their daily needs with basic needs such as primary, secondary and tertiary needs. All of these needs must be accompanied by belief, humans can manage their lives with their belief or religion, therefore religion is one of the human needs that is no less important than these basic needs. By having religion, humans can control everything they face in life, humans can control their passions with the rules of their respective beliefs. This study uses library research, with researchers using a hermeneutic critical discourse analysis approach. This research results in the conclusion that, Religion is closely related to humans, Humans are the most perfect creatures of God because humans have all the elements of other living things plus the mind. Humans need religion because it is human nature. This nature is what causes humans to relate to religion to find their identity.Keyword : People, Needs, and Religion.